Permanent draft genome of strain ESFC-1: ecological genomics of a newly discovered lineage of filamentous diazotrophic cyanobacteria. Issue 1 (December 2016) - Everroad, R.; Stuart, Rhona; Bebout, Brad; Detweiler, Angela; Lee, Jackson; Woebken, Dagmar; Prufert-Bebout, Leslie; Pett-Ridge, Jennifer
Abstract The nonheterocystous filamentous cyanobacterium, strain ESFC-1, is a recently described member of the orderOscillatoriales within theCyanobacteria . ESFC-1 has been shown to be a major diazotroph in the intertidal microbial mat system at Elkhorn Slough, CA, USA. Based on phylogenetic analyses of the 16S RNA gene, ESFC-1 appears to belong to a unique, genus-level divergence; the draft genome sequence of this strain has now been determined. Here we report features of this genome as they relate to the ecological functions and capabilities of strain ESFC-1. The 5, 632, 035 bp genome sequence encodes 4914 protein-coding genes and 92 RNA genes. One striking feature of this cyanobacterium is the apparent lack of either uptake or bi-directional hydrogenases typically expected within a diazotroph. Additionally, a large genomic island is found that contains numerous low GC-content genes and genes related to extracellular polysaccharide production and cell wall synthesis and maintenance.